The Shift Toward a Skills-First Mindset: A Thought-Leader Roundtable. - Rosenblum, Elyse; Ward, Cat; Muench, Jessica; Ahmed, Shad; Raman, Aneesh; Hanson, Teuila (linkedin.com, 2023)
Learn from a panel of experts about skills-first hiring, workforce development, and how to make the shift to a skills-first organization.